DU MOI « CRYPTOPHORE » AU MOI IDENTITAIRE DE NADIA : L’ÉCRITURE THÉRAPEUTIQUE DANS LE ROMAN INSTRUMENTS DES TÉNÈBRES DE NANCY HUSTON - POP, Teodora Maria (Studia Universitatis Babeș-Bolyai Philologia, 2025)
From “Cryptophoric” Subject to Self-Identity: Therapeutic Writing in Nancy Huston’s Instruments des ténèbres. The rupture that occurs in the mother-daughter relationship lies at the core of the novels written by Canadian writer Nancy Huston. In this sense, the present paper aims to analyse Nadia’s identity formation, the protagonist of the novel Instruments of Darkness, who develops a series of mental traumas as a result of maternal abandonment. Starting from the filial bond and from the maternal characteristics transmitted hereditarily, but also acquired through imitation behaviour, our analysis follows the deconstruction of identity self and the consequences over the psyche of the childhood memories repressed in the Unconscious. The mutations of the psychic structures thus lead to split personality and to the configuration of the cryptophore woman’s typology that repeatedly reconstructs the lived traumas: the loss of the mother, the child and the brother. The article follows the identity crisis of the protagonist until the moment of writing, a creative act that involves the externalisation and awareness of repressed feelings and self-acceptance. Having therefore a therapeutic role, literature is analysed as a possible catalyst in the reconstruction of self-identity. REZUMAT. De la eul „criptofor” la eul identitar al Nadiei: scrierea terapeutică în romanul Instruments des ténèbres de Nancy Huston. Nucleul central al romanelor scriitoarei canadiene Nancy Huston este reprezentat de ruptura ce se produce în relația mamă-fiică. Lucrarea de față își propune în acest sens o analiză a parcursului identitar al Nadiei, protagonista romanului Instruments des ténèbres, ce dezvoltă o serie de traumatisme mentale din cauza abandonului matern. Pornind de la raportul filial și de la caracterele materne transmise în mod ereditar, dar și dobândite prin imitarea comportamentului, analiza noastră urmărește deconstrucția eului identitar și consecințele asupra psihicului a amintirilor infantile refulate în Inconștient. Mutațiile structurilor psihice duc spre scindarea personalității și spre configurarea tipologiei de femeie criptoforă ce reconstituie în mod repetat traumele trăite: pierderea mamei, a copilului și a fratelui. Articolul urmărește criza identitară a protagonistei până în momentul scrierii, act creator ce implică exteriorizarea și conștientizarea sentimentelor refulate și acceptarea de sine. Având așadar un rol terapeutic, scrierea este analizată ca un posibil catalizator în reconstrucția eului identitar. Cuvinte-cheie: Nancy Huston, psihologia traumatismului, relația mamă-fiică, identitate și alteritate, catharsis literar, funcția terapeutică a literaturii Article history: Received 27 July 2023; Revised 2 July 2024; Accepted 10 July 2024; Available online 25 March 2025; Available print 30 April 2025.